2014
DOI: 10.3402/rlt.v21.21422
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal profusion in the literacies of the Massive Open Online Course

Abstract: This paper takes a view of digital literacy, which moves beyond a focus on technical methods and skills in an attempt to maintain a broader approach that encompasses a critical view of the learning subject. In doing this, we consider socio-materialism and its relation to aspects of literacy theory. We anchor the discussion in a consideration of the 'E-learning and Digital Cultures' Coursera MOOC, which provided a tangible setting for theorising some of the practices of digital literacy differently. The profusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…In both formal and informal educational contexts, digital citizenship is primarily framed as the ability to effectively make sense of, navigate and exist in the digital world (Hargittai, 2002;Seale and Dutton, 2012). From learning how to access and use digital technologies, to developing 'netiquette' in online interactions, to understanding the ramifications of one's digital footprint, privacy and rights, digital citizenship appears to be synonymous with digital literacy (Knox and Bayne, 2013). By digital literacy we mean 'the capabilities which fit someone for living, learning and working in a digital society' (JISC 22/9/15).…”
Section: The Depoliticisation Of Digital Citizenship and Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In both formal and informal educational contexts, digital citizenship is primarily framed as the ability to effectively make sense of, navigate and exist in the digital world (Hargittai, 2002;Seale and Dutton, 2012). From learning how to access and use digital technologies, to developing 'netiquette' in online interactions, to understanding the ramifications of one's digital footprint, privacy and rights, digital citizenship appears to be synonymous with digital literacy (Knox and Bayne, 2013). By digital literacy we mean 'the capabilities which fit someone for living, learning and working in a digital society' (JISC 22/9/15).…”
Section: The Depoliticisation Of Digital Citizenship and Technologymentioning
confidence: 99%
“…Furthermore, in much of the digital education literature, technology-digital or otherwise-is assumed to possess neutral properties that can simply be harnessed to achieve educators' aims. Consequently, digital technology is excepted from debates about inequality and injustice and not implicated in their reproductions (for example see: Boody, 2001;Gane, 2005; notable exceptions to this are Selwyn, 2008;Knox and Bayne, 2013;Sheail, 2014; In this context, digital citizenship functions as a reaction to technologies operating as disciplining devices compelling individuals and groups to adopt particular skills and ways of being in order to successfully exist in this newly and constantly disrupted world of work and leisure. To be sure, constructing digital citizenship as a lived practice and a social learning process, rather than a conferred status, is important (Lister, 2003;Isin and Neilsen, 2008).…”
Section: The Depoliticisation Of Digital Citizenship and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Os MOOCs são cursos online, abertos, ou seja, sem restrição geográfica, financeira, de idade ou escolaridade (Clair et al, 2015) e massivos, já que milhares de pessoas podem fazer um curso simultaneamente, sendo esta a característica que os difere de outras experiências de e-learning (Sánchez-Vera; Leon;Davis, 2015). Além disso, é interessante considerar o tamanho da rede e a capacidade de gerar novos conhecimentos dos MOOCs, refletindo a aprendizagem participativa e respeitando a diversidade entre o grande número de alunos existentes (Knox;Bayne, 2014).…”
Section: Tecnologia Assistiva No Contexto Educacional E Moocsunclassified
“…Sinfield (2018), in discussing mobile mixed technologies, argues that 'learning is a lifelong experience … pedagogy is applied to communities and not just institutions; thus, … part of this pedagogy becomes greater than the education system within tertiary institutions'. Linear video in its various forms constitute part of the pedagogy of learning in the lifelong learning endeavour, beyond the institution (Knox and Bayne 2013). Tan and Pearce (2011) in investigating free educational resources in their course, including carefully selected YouTube videos, found YouTube videos practical and reported that learners found them worthwhile and interesting.…”
Section: Linear Videos: Youtube As a Learning Technologymentioning
confidence: 99%